Dance to the Music of Time Choreography to the music of Steve Reich reviewed - Winship, Lyndsey (Dance Books Ltd., Alton,Hampshire (UK), 2006)
Review of Steve Reich choreographed. PALABRAS CLAVE: Steve Reich, Anne Teresa De Keersmaeker, Richard Alston, Akram Khan.